Functional Nicotinic Acetylcholine Receptors Containing α6 Subunits Are on GABAergic Neuronal Boutons Adherent to Ventral Tegmental Area Dopamine Neurons - Yang, Kechun (Society for Neuroscience, 2011)
Diverse nicotinic acetylcholine receptor (nAChR) subtypes containing different subunit combinations can be placed on nerve terminals or soma/dendrites in the ventral tegmental area (VTA). nAChR α6 subunit message is abundant in the VTA, but α6*–nAChR cellular localization, function, pharmacology, and roles in cholinergic modulation of dopaminergic (DA) neurons within the VTA are not well understood. Here, we report evidence for α6β2*–nAChR expression on GABA neuronal boutons terminating on VTA DA neurons. α-Conotoxin (α-Ctx) MII labeling coupled with immunocytochemical staining localizes putative α6*–nAChRs to presynaptic GABAergic boutons on acutely dissociated, rat VTA DA neurons. Functionally, acetylcholine (ACh) induces increases in the frequency of bicuculline-, picrotoxin-, and 4-aminopyridine-sensitive miniature IPSCs (mIPSCs) mediated by GABA(A) receptors. These increases are abolished by α6*–nAChR-selective α-Ctx MII or α-Ctx PIA (1 nm) but not by α7 (10 nm methyllycaconitine) or α4* (1 μm dihydro-β-erythroidine)–nAChR-selective antagonists. ACh also fails to increase mIPSC frequency in VTA DA neurons prepared from nAChR β2 knock-out mice. Moreover, ACh induces an α-Ctx PIA-sensitive elevation in intraterminal Ca(2+) in synaptosomes prepared from the rat VTA. Subchronic exposure to 500 nm nicotine reduces ACh-induced GABA release onto the VTA DA neurons, as does 10 d of systemic nicotine exposure. Collectively, these results indicate that α6β2*–nAChRs are located on presynaptic GABAergic boutons within the VTA and modulate GABA release onto DA neurons. These presynaptic α6β2*–nAChRs likely play important roles in nicotinic modulation of DA neuronal activity.